2021
DOI: 10.1002/aelm.202001243
|View full text |Cite
|
Sign up to set email alerts
|

Memristive Devices with Multiple Resistance States Based on the Migration of Protons in α‐MoO3/SrCoO2.5 Stacks

Abstract: Memristive devices are building blocks for neuromorphic computing. However, non‐ideal properties of memristive devices, such as bad retention, small number of resistance states, and nonlinear pulse programming hinder the development of neuromorphic computation. Based on proton migration in the α‐MoO3/SrCoO2.5 stack, a Pt/α‐MoO3/SrCoO2.5/Nb‐SrTiO3 memristive device is developed with multiple resistance states and excellent nonvolatility. When protons migrate from α‐MoO3 to the SrCoO2.5 lattice, both layers unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…6, the BTO/SCO/LSMO bilayers show superior performance compared with other BTO-based films. 26,27,29,34,51–54 In the reliability test, no damage or breakdown of the Pt/BTO/LSMO and Pt/BTO/SCO/LSMO devices was found, as shown in Fig. 5c.…”
Section: Resultsmentioning
confidence: 85%
“…6, the BTO/SCO/LSMO bilayers show superior performance compared with other BTO-based films. 26,27,29,34,51–54 In the reliability test, no damage or breakdown of the Pt/BTO/LSMO and Pt/BTO/SCO/LSMO devices was found, as shown in Fig. 5c.…”
Section: Resultsmentioning
confidence: 85%
“…A two terminal vertical protonic memristive device was reported by Wang et al 39) as shown in Fig. 8 illustrates memory cycling.…”
Section: Two Terminal Vertical Devicesmentioning
confidence: 99%
“…5(c)], bottom electrode act as drain and buried inside proton conductor. [39][40][41][42] In this case, either top electrode or a dedicated layer (placed between top electrode and proton conductor) may act as a source for proton reservoir. By applying electric field between two terminals, migration of protons can be controlled inside proton conducting layer.…”
Section: Structure Of Protonic Synaptic Devicesmentioning
confidence: 99%
“…Depending on the arrangement of atoms, different phases can coexist in solid form, e.g., anatase and rutile phases in TiO 2 [ 116 , 117 ]. Structural changes between phases induce changes in the band structure of the material, resulting in changes in its electrical properties [ 118 126 ]. Materials that exhibit a reversible phase transition upon electrical stimulation can be utilized as a memristor.…”
Section: Operating Principles Of Filament-free Switching Memristorsmentioning
confidence: 99%